Las veedurías ciudadanas como mecanismos efectivos de participación (2013)
The study presented below, an analysis of the effectiveness of citizen oversight and participation mechanisms in the Capital District. In the first instance an approach to the historical context of the subject, thus making the problem formulation. From this, we draw the study objectives and identifies three frameworks, these allow landing theoretical, conceptual and legal citizen control and oversight committees as mechanisms for citizens participation in the country, and in Bogotá D.C. After that, they set out methodologically how to develop objectives, yielding results in a network analysis of Citizen Oversight Committees District, some recommendations regarding the consolidation of the same, and final conclusions of the research topic.